2018
DOI: 10.3390/f9090524
|View full text |Cite
|
Sign up to set email alerts
|

Drought Sensitiveness on Forest Growth in Peninsular Spain and the Balearic Islands

Abstract: Drought is one of the key natural hazards impacting net primary production and tree growth in forest ecosystems. Nonetheless, tree species show different responses to drought events, which make it difficult to adopt fixed tools for monitoring drought impacts under contrasting environmental and climatic conditions. In this study, we assess the response of forest growth and a satellite proxy of the net primary production (NPP) to drought in peninsular Spain and the Balearic Islands, a region characterized by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 88 publications
(119 reference statements)
2
33
1
Order By: Relevance
“…Camarero, Olano, & Parras, 2010; De Luis, Gričar, Čufar, & Raventós, 2007;Gazol, Ribas, Gutiérrez, & Camarero, 2017;Novak et al, 2016;Pasho, Camarero, & Vicente-Serrano, 2012;Peña-Gallardo et al, 2018;Sarris, Christodoulakis, & Körner, 2007) and with the effects of climatic oscillators on tree growth trends in this area (reviewed inCamarero, 2011;Dorado-Liñán et al, 2017;Madrigal-González et al, 2017;Pasho, Camarero, Luis, & Vicente-Serrano, 2011;St George, 2014). Extending this previous evidence, our results highlight a critical importance of sustained, multidecadal negative effects of climatic teleconnections in forest carbon capture and resilience patterns…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Camarero, Olano, & Parras, 2010; De Luis, Gričar, Čufar, & Raventós, 2007;Gazol, Ribas, Gutiérrez, & Camarero, 2017;Novak et al, 2016;Pasho, Camarero, & Vicente-Serrano, 2012;Peña-Gallardo et al, 2018;Sarris, Christodoulakis, & Körner, 2007) and with the effects of climatic oscillators on tree growth trends in this area (reviewed inCamarero, 2011;Dorado-Liñán et al, 2017;Madrigal-González et al, 2017;Pasho, Camarero, Luis, & Vicente-Serrano, 2011;St George, 2014). Extending this previous evidence, our results highlight a critical importance of sustained, multidecadal negative effects of climatic teleconnections in forest carbon capture and resilience patterns…”
supporting
confidence: 76%
“…We suggest that multiple and non-mutually exclusive mechanisms are jointly operating at different timescales shaping the reported trends on forest carbon capture, including the three analysed climatic mechanisms ( Figure 6), and lagged effects of soil hydrological and tree ecophysiological processes. Referring to the ecophysiological processes, major negative effects of drought on the secondary growth of Aleppo pine have been mainly reported at an 8-12 month timescale after drought, but significant effects have been documented for longer time periods (lasting to 24-30 months; Pasho et al, 2011;Peña Gallardo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide additional support to previous studies on forest decline showing that tree growth is constrained by climatic and site conditions, besides being conditioned by structural factors (competition, defoliation, etc. ), in Mediterranean forests [19,57]. The majority of growth studies are based on the traditional forest inventory with diameter measurements.…”
Section: Effect Of Defoliation On Growthmentioning
confidence: 99%
“…Increased foliage removal increased the depression of growth, due to the lack of photosynthate, which is dependent on the amount of live foliage [59], thereby limiting the production of photosynthate available for maintenance and growth [31]. After crown damage, the available starch will be redirected to photosynthetic tissues (e.g., defoliation) instead of radial growth, which exacerbates the mechanisms leading to tree mortality [57,60]. Our findings also demonstrated that the strength of the correlation response of BAI to drought according to the defoliation level.…”
Section: Effect Of Defoliation On Growthmentioning
confidence: 99%
“…Compared to SPI, it considers not only the precipitation supply, but also the atmospheric evaporative demand (Beguería et al, 2010;Vicente-Serrano et al, 2012b). This makes the index more informative of the actual drought effects over various natural systems and socioeconomic sectors (Bachmair et al, 2016;Bachmair et al, 2018;Kumar et al, 2016;Peña-Gallardo et al, 2018a;Peña-Gallardo et al, 2018b;Sun et al, 2018;Sun et al, 2016c;Vicente-Serrano et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%